Lessons Learned from Creating Alert Governance during an Electronic Health Record Transition - Stoffel, Michelle; Desai, Sundeep; Laine, Megan; Leu, Michael G.; Liao, Zachary C.; Jang, Jeehoon; Singh, Angad P.; Pozdeyev, Nikita; Sutton, Paul R.; Wright, Adam; White, Andrew A. (ACI Open, 2022)
Background Our multihospital transition to a single electronic health record (EHR) provided an opportunity to transform alert governance. Our case provides insights into the unique challenges and opportunities of creating governance during a transition to meet both implementation and future alert management needs.ObjectivesThis case report describes the efforts of UW Medicine Information Technology Services to advance alert governance during EHR transition and highlights the opportunities to improve care quality and provider experience within a changing environment.Methods We used a multidisciplinary approach and external evidence to define governance for provider-facing interruptive alerts. We established the context for our governance efforts with a systemic environmental scan. We used literature review and expert consultation to determine alert design and performance best practices, sought to design postimplementation evaluation tools, and engaged clinical stakeholders to help with decision-making.Results We created alert design and implementation tools and an alert approval process, eliminating 21 unnecessary alerts prior to implementation. We developed prototype evaluation metrics and enlisted clinical owners for postimplementation optimization of 221 alerts.Conclusion We leveraged the fluid environment of our EHR implementation to rapidly build a provider-led governance infrastructure to meet immediate transitional needs and to facilitate future alert maintenance and improvement.
Keywords: clinical decision support; alerting; governance